Zinc isotope fractionation by Emiliania huxleyi cultured across a range of free zinc ion concentrations. (18th September 2017) - Samanta, Moneesha; Ellwood, Michael J.; Strzepek, Robert F.
Abstract: Zinc (Zn) isotope fractionation by the coccolithophore Emiliania huxleyi (a Tasman Sea isolate) was investigated by culturing it across a range of free Zn 2+ ion concentrations (1.2 pmol L −1 to 3.2 nmol L −1 ), which span the natural range observed in the global oceans. Across the range of free Zn 2+ ion concentrations tested, the amount of bio‐available Zn did not have any appreciable influence on the specific growth rate or cell morphology of E. huxleyi . However, a suite of secondary physiological indicators reflected changes in Zn bioavailability. An increase in the photosynthetic efficiency of photosystem II ( F v / F m ) was observed with increasing free Zn 2+ ion concentration. The time constants for electron transport from QA to QB and from QB to the plastoquinone (PQ) pool decreased as the free Zn 2+ ion concentration increased, reflecting enhanced photosynthetic electron transport. The effect of Zn bioavailability on photosynthetic physiology was speculated to be due to increased activity of carbonic anhydrase with increasing Zn bioavailability. Zinc uptake by E. huxleyi resulted in Zn isotope fractionation and the Δ 66 Zncells‐media ranged between −0.6‰ and −0.2‰. The major finding from this work is that the lighter Zn isotope is taken up preferentially by this coccolithophore, making the dissolved Zn composition of the surrounding seawater isotopically heavier.